Management of municipal solid waste using the SWOT model (Case study: Mahshahr Petrochemical Special Economic Zone) - Lotfallah Bovard; maryam ilanloo (نشریه جغرافیا و برنامه‌ریزی, 2020)
Today, with the increase of waste production in urban and rural communities, the waste management system can be considered as part of comprehensive management systems. Basically, establishing a solid waste management system is one of the things that matters to control the production, consumption and consumption of materials, as well as the process of collecting and disposing of waste. the economic and health damage caused by the uncontrolled control of solid waste in the Mahshahr Petrochemical Special Economic Zone explains the need to take substantive steps in the control of solid waste. this research is aimed at the management of solid urban waste and its role in sustainable development in the special economic area of petrochemical in Mahshahr city. the research data are mainly collected through fieldwork. according to the obtained data, the status of municipal solid waste management was studied. The SWOT model was used to analyze the findings. for this purpose, the internal environment (strengths and weaknesses) and the external environment (opportunities and threats) of the region were studied. then, in order to complete the o-btained data, a questionnaire was prepared by citizens and staff of Mahshahr Petrochemical Special Economic Zone, which, by weighting the desired items, completed the SWOT matrix, finally, presented the strategies and strategies for proper management of the collection. and disposal of wastes. the results of this study showed that the questionnaire survey showed that respondents of municipal solid waste management situation in Mahshahr petrochemical specialty region are more suitable for most parameters and that management and proper planning of waste management of the special economic zone organization of petrochemical are economically justified.